2019
DOI: 10.1111/jdi.13045
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned media from dental pulp stem cells improved diabetic polyneuropathy through anti‐inflammatory, neuroprotective and angiogenic actions: Cell‐free regenerative medicine for diabetic polyneuropathy

Abstract: Aims/Introduction Dental pulp stem cells (DPSCs) can be easily obtained from teeth for general orthodontic reasons. We have previously reported the therapeutic effects of DPSC transplantation for diabetic polyneuropathy. As abundant secretomes from DPSCs are considered to play a central role in the improvement of diabetic polyneuropathy, we investigated whether direct injection of DPSC‐conditioned media (DPSC‐CM) into hindlimb skeletal muscles ameliorates diabetic polyneuropathy in diabetic rats. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 43 publications
0
37
0
1
Order By: Relevance
“…Dental pulp MSC-CM improved neuromuscular junction innervation and motor neuron survival in treating amyotrophic lateral sclerosis through different trophic factors and cytokines [149]. Similarly, dental pulp MSC-CM exhibited neuroprotective, anti-inflammatory, and angiogenic actions when administrated into unilateral hind limb skeletal muscles of a diabetic polyneuropathy rat model [150]. Intrathecal administration of dental pulp MSC-CM in a rat aneurysmal subarachnoid hemorrhage model revealed improvement in cognitive and motor impairments, microcirculation, and reduction of neuroinflammation.…”
Section: Dental Pulp Msc-cm In the Therapy Of Neural Disordersmentioning
confidence: 96%
“…Dental pulp MSC-CM improved neuromuscular junction innervation and motor neuron survival in treating amyotrophic lateral sclerosis through different trophic factors and cytokines [149]. Similarly, dental pulp MSC-CM exhibited neuroprotective, anti-inflammatory, and angiogenic actions when administrated into unilateral hind limb skeletal muscles of a diabetic polyneuropathy rat model [150]. Intrathecal administration of dental pulp MSC-CM in a rat aneurysmal subarachnoid hemorrhage model revealed improvement in cognitive and motor impairments, microcirculation, and reduction of neuroinflammation.…”
Section: Dental Pulp Msc-cm In the Therapy Of Neural Disordersmentioning
confidence: 96%
“…It has been shown that conditioned medium obtained from MSCs has therapeutic effects in several somatic disorders [ 140 , 141 ]. Conditioned medium from DPSCs and SHEDs have also been clarified to have regenerative potential [ 142 , 143 , 144 , 145 ]. Although the main substance contained in conditioned medium and exerting therapeutic effects has not been clarified, exosomes might play an important role in regenerative processes.…”
Section: Regenerative Capacity Of Dpscs and Shedsmentioning
confidence: 99%
“…Currently, the therapeutic mechanism of progenitor/stem cell transplantation is considered to be mainly associated with the abundant secretomes of transplanted stem cells in the early phase of transplantation. According to the hypothesis of secretomes, we investigated the effects of DPSC-SF administration on diabetic polyneuropathy [ 19 ]. We confirmed that DPSC-SF administration ameliorates sciatic nerve conduction velocity, sciatic nerve blood flow, and intraepidermal nerve fiber density, as well as the capillary/muscle bundle ratio, in the skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were anesthetized with isoflurane and placed on a heated pad in a room maintained at 25 °C, and the near-nerve temperature was maintained at 37 °C using a BAT-12 multipurpose thermometer (Bioresearch Co. Nagoya, Japan). MNCV between the ankle and the sciatic notch and SNCV between the ankle and the knee were measured by a Neuropak MEB-9400 instrument (Nihon-Koden, Osaka, Japan) as described previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation